Analysing substitutional patterns on demand for poultry meat in South Africa - Jörnling, Angelica (2017)
In recent years, large quantities of poultry meat have been dumped in the South African mar-ket by suppliers in other countries, such as Brazil, USA and the EU, at prices way below the domestic cost of production, threatening local producers and jobs. Therefore, South Africa has imposed countervailing anti-dumping duties on these foreign suppliers in order to protect its domestic poultry sector. In order to develop better understanding of demand relationships among domestic and foreign poultry suppliers to the South African market, this study has empirically estimated the elasticity of substitution between imported and domestically pro-duced poultry meat. The results reveal that the elasticity of substitution ranges between 6.49 and 6.63, indicating that an increase in the prices of the domestically produced poultry meat would lead to a reduce in demand for domestic poultry meat and curtail the expenditure on the product. Hence, domestically produced and imported poultry meat are considered to be similar to the South African households, which indicates that the products can be substituted and are therefore also sensitive to price changes. The elasticity of substitution can be seen as a key parameter to analyse the impacts of these imposed anti-dumping duties.